Javanese Women's Gender Reconstruction in Bumi Manusia Film - Anggun Mayanti; Haryono, Cosmas Gatot (Jurnal Spektrum Komunikasi, 2023)
The film cannot be viewed solely as a form of entertainment. However, the media plays the role of social reality construction. The film Bumi Manusia, which uniquely depicts the female gender, is full of social construction roles. The female character in the film, Nyai Ontosoroh, is described as having different characteristics and abilities than Javanese women in the nineteenth century. As a result, researchers want to examine the film to see how the reconstruction of women's gender occurs in it. The researcher used a qualitative method based on Ferdinand de Saussure's semiotic approach. According to the research findings, this film aims to rebuild women's gender roles and positions that are equal to those of men. Women are figures with equal strength and ideas to men, particularly in leadership, which has traditionally been dominated by men. Nyai Ontosoroh, as a female gender representative, is portrayed as a new reality with strong characters: resilient, not easily defeated, knowledgeable, and capable of leadership. It is hoped that this reconstruction of Nyai Ontosoroh's figure will help to dispel the old stereotype of women as weak, capable of only makeup (macak), cooking (masak), and (giving birth) manak.